Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1371/journal.pone.0016827
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Sialoadhesin (CD169/Siglec-1) Is an Endocytic Receptor that Allows Targeted Delivery of Toxins and Antigens to Macrophages

Abstract: Sialoadhesin is exclusively expressed on specific subpopulations of macrophages. Since sialoadhesin-positive macrophages are involved in inflammatory autoimmune diseases, such as multiple sclerosis, and potentially in the generation of immune responses, targeted delivery of drugs, toxins or antigens via sialoadhesin-specific immunoconjugates may prove a useful therapeutic strategy. Originally, sialoadhesin was characterized as a lymphocyte adhesion molecule, though recently its involvement in internalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 71 publications
3
82
1
1
Order By: Relevance
“…1C). By flow-cytometric analysis, the surface-bound antibodies were measured before and after induction of internalization to allow a more quantitative measurement of internalization (33,34). For HEp-2 cells and A549 cells, the mean fluorescence intensity (MFI) of surface RSV proteins after the addition of antibodies was reduced to 44% and 40%, respectively, showing that internalization occurs but that not all RSV proteins are internalized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1C). By flow-cytometric analysis, the surface-bound antibodies were measured before and after induction of internalization to allow a more quantitative measurement of internalization (33,34). For HEp-2 cells and A549 cells, the mean fluorescence intensity (MFI) of surface RSV proteins after the addition of antibodies was reduced to 44% and 40%, respectively, showing that internalization occurs but that not all RSV proteins are internalized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies showed that pCD163 cooperated with another putative receptor, porcine sialoadhesin (Sn/CD169) (23), to facilitate the PRRSV infection, where the former contributed to the uncoating of PRRSV while the latter promoted the attachment and internalization (invasion) of the virus (40)(41)(42)(43)(44)(45)(46)(47)(48). However, one study showed that Sn gene knockout pigs were infected by PRRSV as usual (49), and a recent study using geneedited pigs demonstrates the indispensability of pCD163 (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to primarily function in mediating macrophage-pathogen adhesion and phagocytosis [30] as well as in promoting antigen presentation [31]. Siglec1 does not contain any known cytosolic motifs to mediate inhibitory signaling itself, and the interaction between Siglec1 and intracellular regulators is poorly understood.…”
Section: Discussionmentioning
confidence: 99%